Penguatan Pembelajaran Daring Melalui Pelatihan Penggunaan Aplikasi Canva - Annas Al Fiani; Muhamad Hanif (Jurnal Pengabdian Masyarakat PGSD, 2022)
The occurrence of the Covid-19 pandemic has made the learning system in Indonesia change from offline to online. Online learning requires teachers to creatively and innovatively deliver subject matter because online learning depends on the ability to use technology. Some teachers at the Islamic Elementary School of Sirojul Athfal have not been able to use technology properly and faced difficulty to make learning media so which creates monotonous learning and makes students less interested in teaching and learning. Hence, students do not understand the material presented. To the problem above, the author held training on the Canva application used to support learning media creation for teachers at the Islamic Elementary School of Sirojul Athfal, Limo sub-district, Depok city. The method used in this activity is to provide training on how to use the Canva application. This activity is intended so that teachers can use the Canva application to create a variety of fun learning media to make students interested in participating in teaching and learning activities. Canva is a graphic design application that can be used to create digital learning media such as interactive presentations, e-modules, learning comics, educational posters, and so on. This training was carried out from early July until the end of July 2021 through an offline class at the Islamic Elementary School of Sirojul Athfal. The program targets in this activity were 2 teachers. Through this training activity, teachers can create interactive and fun learning media for students so that they can attract students' interest in learning The teacher feels this activity is very useful and hopes to continue.